Effects of row spacing and planting density of beans on seed quality - Lollato, Marco Antonio; Faria, Rogério Teixeira de; Silva, Walter Rodrigues da (Pesquisa Agropecuaria Brasileira, 2014)
During 1978, experiments were conducted in Irati, Ivaiporã and Siqueira Campos in Paraná State, Brazil, to evaluate the effects of row spacing and plant density on and quality of bean (Phaseolus vulgaris L.) cv. ’Carioca’, Aroana’ and ’Goiano Precoce’, in the dry season of 1978, wet season of 1978/79, and dry season of 1979. Row spacing of 80, 60, 48 and 40 cm were studied for ’Carioca’ and ’Aroana’ and 60, 48, 40 and 30 cm for ’Goiano Precoce’, and plant density of 10, 15 and 20 plants per meter. The results showed that row spacing had an effect on individual and weight, wider spacing resulting in heavier seed. Effect of plant density was only observed for cv. ’Aroana’ as to the infected seedling number, less dense population resulting in less number of infected seedlings. The germination test, accelerated aging test, and seed depletion test did not show any effect of row spacing and plant density upon physiological quality of seeds.